Vulnerabilidad y riesgo por inundaciones en la microcuenca media del río Quevedo - Montufar Falcon , Adrian Alberto (2023)
Analyzing vulnerability to floods in in the canton of Quevedo is a valuable tool for planning strategies and actions to mitigate the damage caused by this natural phenomenon. The identification of the most vulnerable sectors is fundamental for implementing preventive measures and preparing the population and infrastructure to face floods. In addition, the combination of physical, social, and economic criteria provides a more complete picture of the population's vulnerability and allows better decisions to be made. These criteria include the topography of the terrain, population density, the existence of critical infrastructure, the presence of urban, industrial, or agricultural areas, and the economic capacity of the communities to respond to and recover from a flood event. The results were presented by levels, with 34,10% being very high, representing an area of 10388,72 ha of the study site, followed by 27% at a very low level, corresponding to 8274.52 ha. A total of 18,27% of the study area, corresponding to 5565,65 ha, has a low level, while the medium and high levels correspond to 5,30% and 15,17%, occupying areas of 1614,29 ha and 4621,03 ha, respectively. In terms of physical, social, and economic vulnerability, Quevedo canton has a medium level. It is important to note that the periodic evaluation of vulnerability to floods is essential to be able to adapt to changes that may occur in the future. Key words: multi-criteria evaluation, evaluation criteria, raster images, strategy.